Presentations (Boston, 2014)
Feeling stressed about your upcoming presentation? Whether you're nervous abuot how you'll organize your thoughts or how you'll articulate them on the big day, Presentations provides the quick guidelines and expert tips you need to craft your message, prepare and rehearse effectively, engage your audience, manage Q&A sessions.
Keywords: Thuyết trình kinh doanh,Business presentations